Partisipasi Masyarakat dalam Penanggulangan Stunting melalui Kegiatan Gizi Puskesmas Kebong Kecamatan Kelam Permai - Listiani, Endang Indri; Yulianti, Yulianti; Patriani, Ira (Eksos, 2023)
The purpose of this study was to find out the form of community participation in stunting prevention through nutrition activities at Kebong Health Center, Kelam Permai District and to find out what factors influenced community participation in stunting prevention through nutrition activities at Kebong Health Center, Kelam Permai District. The research method used was descriptive research with a qualitative approach. In this study, the primary data source was data collected directly from the village government, health center, village communities in the Kelam sub-district, as parties related to the stunting management process. The results of the study explain that community participation in the nutrition program for stunting prevention by the Kebong Health Center, Kelam Permai District, namely: Campaign and Declaration of Stunting Prevention, Toddler Posyandu, Tracking of Stunted Babies, Malnutrition Surveillance, Implementation of Pregnant and Toddler Classes, Assistance of Pregnant Resti, Surveillance of Pregnant Women KEK , and the Exclusive Breastfeeding Group, as well as Monev for Stunting Toddlers. Forms of Community Participation in the form of: Labor Participation, Skills Participation, and Social Participation. Stages of community participation in the form of: Participation in Implementation, Participation in Evaluation, and Participation in Taking Benefits. Levels of Community Participation starting from: Consultation, Making joint decisions, Acting together, Providing support. Factors that influence community participation in the nutrition program for stunting control in Kelam Permai District are government intervention, community awareness, close living quarters, and free programs and The inhibiting factors were low knowledge, parents' work, lack of socialization, and inadequate follow-up.